Timor-Leste Public Financial Management: Progress And Challenges - Olinda Da Cruz Alves; Desni Mariani Oematan (Jurnal Publikasi Ilmu Manajemen, 2024)
Since gaining independence, Timor-Leste has demonstrated suboptimal public financial management in handling oil revenues. Over the past two decades, Timor-Leste has relied on oil funds as the backbone of its economy, accounting for up to 80% of the national budget each year. As a consequence, Timor-Leste faces issues arising from this dependency on oil revenues. This research aims to determine the effectiveness of public financial management in Timor-Leste in managing the national budget to support the livelihoods of its citizens. This study employs a qualitative descriptive method to comprehensively describe the existing data. The results indicate public financial management by the Timor-Leste government in handling oil funds. The government has even invited foreign investors from countries such as Indonesia and China to develop infrastructure in Timor-Leste. However, despite these foreign investments, Timor-Leste has yet to create job opportunities that can absorb the existing labor force and sustainably drive the economy.